Lombok Folktales Dari Datu Pejanggiq Sampai Putri Mandalika as Literacy Support in Elementary Schools - Rina Sudaryani; Purwati Zisca Diana; Yosi Wulandari; Iis Suwartini (Jurusan Tadris Bahasa Indonesia, 2024)
This research aims to develop a collection of Lombok folktales titled